LGBTQ+ CONSTRUCTION ON THE #FREETOLOVE CAMPAIGN IN CLOSE UP ADVERTISEMENT - Henni Gusfa; Ramdani; Stella Monica Franciska (Universidade Feevale, 2021)
The purpose of this study was to investigate the meaning construction of the signs contained in the #FreeToLove campaign in the Close Up advertisement that constructs LGBTQ+. This study applies both Ferdinand De Saussure's theory and methodology. The analysis was deeply discussed on the #FreeToLove campaign from the advertisement shot which was considered to construct the Lesbian, Gay, Bisexual, Transgender, Queer, and Others (LGBTQ+) sign through the verbal aspect in the Close Up advertisement. This campaign aims to show and fight for different types of love and mutual respect for all love on various platforms ranging from couples of different ages, social caste/class, culture/race, religion, and even same-sex relationships. In the advertisement, same-sex relationship elements are seen to be more dominant than other elements. The formation of the idea originated from the existence of a declaration legalizing LGBT that has been included in the law and given protection. The campaign's prejudice was more towards LGBTQ+ when Unilever, which is the owner of Close Up, also supported LGBTQ + and through the Close Up brand, which represented the closeness of the #FreeToLove campaign, began campaigning and producing advertisements and films. Prejudice can lead to acts of discrimination that can be detrimental. LGBTQ+ symbols have been included in advertisements to create a new culture that leads people to know about their existence. People who didn't know before can find out through a Close Up ad campaign in 274 places in the world.